The orthodox liturgical year and its theological structure - Streza, Dan A. (HTS teologiese studies, 2021)
The concept of ‘liturgical year’ indicates a reference to the meaning of the measuring units of civil time, and especially to the cosmic entities that determine the general rhythm of time – the sun and the moon. Interestingly, the liturgical time depends both on the structure of civil time, and, on the two discrete systems of the solar and lunar cycles, which have always been underpinnings of time measuring. The special importance and influence that the cosmical rhythms exert on the entire human life are also felt in the structure and theology of the liturgical time, where it signals the attempt to merge and reconcile the cosmical solar and lunar cycles within the liturgical year. This leads to a unique theology, expressing the powerful synthesis of the variability of the lunar cycle compared to the structure of the solar year’s fixed dates.Contribution: This research reveals the unique orthodox perspective on both civil and liturgical time, expressing their profound theological meaning, as a conscious, permanent reflection upon the mysterious, yet real, presence of Christ in the divine services of the Church.